Could someone explain to me as simply as possible how to factorise
2x^2 + x - 3
I know the answer is (2x + 3) (x - 1) from my textbook but I don't understand the method used.
$\displaystyle (\pm\alpha x\pm\beta)(\pm\lambda x\pm\phi)$
$\displaystyle \beta*\phi=-3\Rightarrow 3*1=3$ Now need to figure out which one is negative.
$\displaystyle \alpha*\lambda=2\Rightarrow 2*1=2$
$\displaystyle \alpha*\phi+\beta*\lambda=1$
Now you need to decide if 3 is beta and 1 is phi, is alpha 1 or 2 and is lambda 1 or 2?